North Pacific Security Regimes: the North Pacific Cooperative Security Dialogue and Open Skies - Chong, Allen K. (My University, 1992)
This thesis examines the likelihood of institutionalized security arrangements, which have been successfully developed in Europe, emerging in the North Pacific. It seeks to explain whether a security regime, involving confidence and security building measures (CSBMs) or arms control, can be established in the region. If such a regime is to be established, the obstacles that have to be overcome are analyzed. As a way of testing the transferability of CSBMs from Europe to the North Pacific, two regional CSBM proposals, the North Pacific Cooperative Security Dialogue (NPCSD) and Open Skies (OS), are evaluated. It is concluded that the NPCSD is more likely to succeed, as a regional security regime, than an attempt to transplant the Open Skies concept from Europe to the North Pacific.
Given the problems between the various North Pacific states and the different circumstances between the North Pacific and Europe, the NPCSD is more likely to be adopted because it attempts to build the requisite political cooperation necessary for larger CSBMs, like Open Skies, to work. Open Skies needs greater inter-state collaboration than currently available in the region. This thesis concludes with a discussion of how greater economic integraton of the North Pacific political-economy might encourage political cooperaton over regional issues.
Keywords: Political Science; Political Science